Aree Interne tra Deagrarizzazione e Riagrarizzazione: Giovani Agricoltori e Meccanismi di Ritorno all’ “Osso” in Centro Sardegna - Uleri, Francesca; Meloni, Benedetto; Piccoli, Alessandra; Elsen, Susanne (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
The presence and coexistence of deagrarianization and reagrarianization movements within Italian Inner Areas implies the adoption of keys to understanding their evolution that take into account both processes that generate the so-called "voids" (e.g. demographic decline, erosion of territorial capital, etc.) and processes of territorial resistance and renaissance. Accordingly, the paper explores the nature and peculiarities of both movements in Central Sardinia, specifically in the territories of Barbagia, Mandrolisai and Ogliastra. Empirically, it focuses on the mechanisms that characterize a young farmers’ back-to-the-land process by individuating the motivational aspects that determine the choices for starting an agricultural business for the first time or taking over an existing farm, and identifying the elements that place the action of the farm beyond its perimeter, in an articulated system in which the new agrarization is a pivotal element of a broad process of territorial regeneration and reconnection with urban areas.